2008
DOI: 10.1210/jc.2007-1559
|View full text |Cite
|
Sign up to set email alerts
|

Anastrozole Increases Predicted Adult Height of Short Adolescent Males Treated with Growth Hormone: A Randomized, Placebo-Controlled, Multicenter Trial for One to Three Years

Abstract: Anastrozole increases adult height potential of adolescent boys on GH therapy while maintaining normal pubertal progression after 2-3 yr. This treatment offers an alternative in promoting growth in GH-deficient boys in puberty. Long-term follow up is needed to elucidate fully the safety and efficacy of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 47 publications
6
74
2
8
Order By: Relevance
“…Over the past decades there has been a dramatic rise in the age-adjusted incidence of cutaneous squamous cell carcinoma (SCC) in Western countries [1,2,3], which has been associated with increased ultraviolet light exposure, due to lifestyle and global environmental changes [4,5,6]. Morbidity and costs associated with the treatment of cutaneous SCC have an important impact on health systems in areas with a higher incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades there has been a dramatic rise in the age-adjusted incidence of cutaneous squamous cell carcinoma (SCC) in Western countries [1,2,3], which has been associated with increased ultraviolet light exposure, due to lifestyle and global environmental changes [4,5,6]. Morbidity and costs associated with the treatment of cutaneous SCC have an important impact on health systems in areas with a higher incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although only short-term follow-up is still available, these controlled clinical trials have provided a good safety profile for treatment with aromatase inhibitors. No adverse effects have been demonstrated on glucose, plasma lipid concentrations, and insulin sensitivity (20,23), spermatogenesis (24), and cognitive function (25). Additionally, aromatase inhibitors did not induce detrimental effects on bone mineral density (19,20,26).…”
Section: Discussionmentioning
confidence: 93%
“…No adverse effects have been demonstrated on glucose, plasma lipid concentrations, and insulin sensitivity (20,23), spermatogenesis (24), and cognitive function (25). Additionally, aromatase inhibitors did not induce detrimental effects on bone mineral density (19,20,26). A more recent report suggested that boys with idiopathic short stature treated with letrozole might be predisposed to asymptomatic vertebral wedge deformities (27), although the relevance of these findings is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BHE'de BH tedavisine ek olarak erkeklerde aromataz inhibitörü tedavisi ile çalış-malar olmakla beraber, yeterli etkinlik ve güvenirlik verisi yoktur ve rutin uygulama önerilmemektedir (41) . Sonuç olarak, puberteye kısa boy ile giren BHE tanılı çocuklarda, toplam pubertal boy kazanımını artırmak hala zor olduğundan, optimal tedavi prepubertal dönemde büyümenin yakalanması ve puberte başla-madan normal boya erişime olanak sağlayan tedavi olacaktır.…”
Section: Toplam Pubertal Büyümeyi Artırmaya Yönelik Tedavi Yaklaşımlarıunclassified